Demam tifoid sistemik yang disebabkan oleh Salmonella gallinarum pada ayam broiler: Bukti patologis dan mikrobiologis - Azzahra, Tiara; Maharani, Devina Aisyah; Tsevaot, Amar Adonay; Hartady, Tyagita; Prayugo, Armanda Dwi; Windria, Sarasati; Krissanti, Ita; Satrio, Faisal Amri (School of Veterinary Medicine and Biomedical Sciences, Bogor Agricultural University, 2025)
Salmonella gallinarum, the causative agent of fowl typhoid, is a highly pathogenic bacterial disease associated with substantial mortality in poultry, predominantly affecting adult chickens and turkeys. This study aimed to describe the pathological lesions and microbiological characteristics of S. gallinarum infection in chickens with fowl typhoid. S. gallinarum is a gram-negative, rod-shaped, facultative anaerobic bacterium with an optimal growth temperature of 37 °C and the ability to survive across a broad pH range (4.0–9.0). Necropsy findings in affected chickens revealed interstitial pneumonia of the lungs, intestinal hyperemia with petechial hemorrhages, hepatomegaly, splenomegaly, and fatty degeneration of the cardiac tissue. Bacterial culture of intestinal swab samples on MacConkey agar demonstrated the growth of pale-yellow colonies consistent with S. gallinarum. Microscopic examination confirmed Gram-negative bacilli, while biochemical testing showed an alkaline/acid reaction, absence of gas and H₂S production, non-motility, and negative indole and urease reactions